(untitled) - Carter, Thomas Francis (New York, 1925)
Revised edition with an introduction by Douglas McMurtrie on Carter. A very important book in the study of the history of printing.
Keywords: Printing,Printing,Nghề in ấn,Nghề in ấn; History,Origin and antecedents,History,Lịch sử,Tiền đề và nguồn gốc,Lịch sử; China,Trung Quốc